2019
DOI: 10.1093/mnras/stz2867
|View full text |Cite
|
Sign up to set email alerts
|

What information can we derive from historical Far Eastern guest stars for modern research on novae and cataclysmic variables?

Abstract: Recently, there have been several studies on the evolution of binary systems using historical data treated as facts in the chain of arguments. In this paper we discuss six case studies of modern dwarf novae with suggested historical counterpart from the historical point of view as well as the derived consequences for the physics of close binary systems (the dwarf novae Z Cam and AT Cnc, the nebula in M22, and the possible Nova 101, Nova 483, and Nova 1437). We consider the historical Far Eastern reports and af… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…This was the first CV unmasked as an ancient nova (Shara et al 2007) and it is still the oldest, with an estimated age of 1300 to ≥5000 yr (Shara et al 2012a). It has been suggested that it can be identified with a guest star from the year 77 BCE as recorded by Chinese astrologers (Johansson 2007), but this has been recently disputed by Hoffmann (2019). Unfortunately, the Z Cam shell so far has only been analysed in terms of extension and expansion, but not in flux, so that it cannot be used in the context of the present paper.…”
Section: Z Cammentioning
confidence: 98%
See 1 more Smart Citation
“…This was the first CV unmasked as an ancient nova (Shara et al 2007) and it is still the oldest, with an estimated age of 1300 to ≥5000 yr (Shara et al 2012a). It has been suggested that it can be identified with a guest star from the year 77 BCE as recorded by Chinese astrologers (Johansson 2007), but this has been recently disputed by Hoffmann (2019). Unfortunately, the Z Cam shell so far has only been analysed in terms of extension and expansion, but not in flux, so that it cannot be used in the context of the present paper.…”
Section: Z Cammentioning
confidence: 98%
“…For the lack of a more precise and poignant term, we call those systems 'ancient novae', although this should not be taken strictly in the sense of an age indicator. Still, typically these nova eruptions will have occurred in epochs that predate the known nova eruptions and could, perhaps, be dated in some cases if a historical Far Eastern Guest star can be identified with a modern CV as classical nova candidate (Vogt et al 2019;Hoffmann 2019). Determining the luminosity of their shells would, thus, extend the time axis beyond the D01 data and provide important information on the late stages of the luminosity evolution.…”
Section: Ancient Novaementioning
confidence: 99%
“…The analysis of historical astronomical records has become an important resource for research on long-term variability of stars (Fujiwara et al 2004;Fujiwara and Yamaoka 2005;Hamacher and Frew 2010;Hamacher 2018), comet orbits (Neuhäuser et al 2018), meteoritic events (Hamacher 2009), novae (Shara et al 2007;Duerbeck 2008;Patterson et al 2013;Miszalski et al 2016;Shara et al 2017), supernovae (Stephenson 1976;Clark and Stephenson 1977;Yau 1988;Stephenson and Green 2002;Green and Stephenson 2003;2017;Zhou et al 2018;Green 2019) and close interacting binary stars. Stellarium can be used to demonstrate transient phenomena like comets or "guest stars" recorded by historians and chroniclers (Zotti and Wolf 2020a;Hoffmann 2019b;Hoffmann et al 2020;Hoffmann and Vogt 2020a).…”
Section: Skycultures and Astrophysicsmentioning
confidence: 99%
“…Assuming optimistically a (faint) detection limit of five mag appearances for naked eye observers (which certainly does not apply at least in regions of bright celestial background as in the clouds of the Milky Way: cf. Hoffmann (), Figure A3 for the error or estimating stellar magnitudes, and Figure .) a CV candidate should have a current apparent brightness of 5 + 16 = 21 mag.…”
Section: Localization Of Historical Sightingsmentioning
confidence: 99%
“…Concerning the descriptions of positions in historical reports, we want to point out that there are no coordinates before the 17th century but only verbal descriptions with regard to Chinese asterisms (Hoffmann ). Chinese asterisms can either be one single star or a group of stars, which we would name a constellation in western cultures).…”
Section: Introductionmentioning
confidence: 99%